PENGARUH BAURAN PROMOSI TERHADAP CITRA PRODUK PADA PT. DJOJONEGORO C-1000 - Supardi Supardi (Jurnal Ekonologi Ilmu Manajemen, 2019)
The purpose of the study was to determine the promotional mix containing advertising, sales promotion, public relations, personal sales and direct marketing of product images as well as major considerations related to the promotion of advertising mix, sales promotion, public relations, personal sales and direct marketing of product images. Respondents in this study were 50 people based on the sampling technique carried out on a non probability sampling by incidental sampling technique with a population of 500 people. The research method used is Descriptive and Associative Method, which discusses using Spearman rank analysis and testing hypotheses, with t-test, besides that also conducted Reliability test to find out in testing and testing the Validity to find out how to use data correctly. Promotion, Sales Promotion, Public Relations, Personal Sales, and Direct Marketing based on classification fall into the very good category with an average in a good category with a weighting average of 234. which is quite strong between the promotion mix that includes advertising, sales promotion, relationships community, personal sales and direct marketing of product images, with a resistance coefficient = 0.468. From the calculation results it can be seen that the Determination coefficient = 82%, and the results of the t-test for the two-party test at a significance level of α = 5% obtained the value of t count greater than the price of t table (3,668> 1,996), then Ho is accepted and Ha is accepted . This shows an increase in the mix of promotions that add advertising, sales promotion, public relations, personal sales and direct marketing has also increased the product image.